دراسة تأثير الفعل التآزري للمضافات في زيادة مقاومة أحتراق راتنج ألايبوكسي - عباس حسن فارس; حميد كاظم عباس; منتهى نعمة الثويني (Journal of Madenat Alelem University College, 2012)
Abstract In this work three additives were used as flame retardants in different weight percentage (0, 1,3,5,7.5,10) with epoxy resin. They are: 1- Calcium carbonate (I) 2- Chlorinated paraffin ( II ) and 3- Calcium carbonate with chlorinated paraffin (50:50) (III). The study included the following tests in order to determine the effectiveness of the used additives to increase the combustion resistance and decrease the flammability of epoxy resin. Measurement of limiting oxygen index (LOI) according to ASTM: D-2863, measurement of rate of burning (R.B), burning extent (E.B), and burning time (T.B) according to ASTM: D-635. Results indicated that the additives (I, II, III,) were active to inhibited burning and reduce the flammability of epoxy resin. Their effectiveness follows the following order: III> I >II. The compatibility of additives with epoxy resin was also taking in consideration because the compatibility is a main factor in the flame retardancy of any polymer, which reflects the distribution of additives (flame retardants) in the epoxy resin systems prepared in this study. The overall conclusion of this study indicated that all the percentages of the flame retardants used with epoxy resin have for some extent (low or high) a good effect to reduce the flammability and increase the fire resistance of epoxy resin. As the percentage of additives increase, the polymer system will be non-burning system and self-extinguishing (e.g. 7.5% and 10%).